2013
DOI: 10.2340/16501977-1069
|View full text |Cite
|
Sign up to set email alerts
|

Measure for the assessment of confidence with manual wheelchair use (WheelCon-M) version 2.1: Reliability and validity

Abstract: WheelCon-M 2.1 has high internal consistency, strong retest reliability, and support for concurrent validity, construct validity and responsiveness. This new test holds promise as a clinical and research tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…The relationship among wheelchair confidence, wheelchair skills and life-space mobility is not unexpected, because self-efficacy has been hypothesized to moderate the relationship between capacity and performance (26). A similar relationship among wheelchair skills, lifespace mobility and frequency of participation has been found among facility residents who use wheelchairs as their primary means of mobility (20,39).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The relationship among wheelchair confidence, wheelchair skills and life-space mobility is not unexpected, because self-efficacy has been hypothesized to moderate the relationship between capacity and performance (26). A similar relationship among wheelchair skills, lifespace mobility and frequency of participation has been found among facility residents who use wheelchairs as their primary means of mobility (20,39).…”
Section: Discussionmentioning
confidence: 80%
“…Similar moderate correlations between wheelchair confidence and objective wheelchair skills have been observed among manual wheelchair users. (38,39). Wheelchair confidence was also associated with perceived difficulty in participation (ATOP/M-P) and had he fifth strongest association.…”
Section: Discussionmentioning
confidence: 96%
“…The 65-item version 3.0 was used in study 1, and the 63-item version 2.4 was used in study 2 2 . In this study, the 60 similar items in both versions of the WheelCon were retained for analyses, as were the 5 new items in the WheelCon version 3.0.…”
Section: The Wheelchair Use Confidence Scalementioning
confidence: 99%
“…Evidence using Classical Test Theory methods indicates that the WheelCon measurements are both reliable and valid in manual wheelchair-users. 2 Furthermore, research using the WheelCon has shown that lower self-efficacy is associated with lower levels of participation frequency 3,4 and life-space mobility 5 in wheelchair-users aged 50 and older.…”
mentioning
confidence: 99%
See 1 more Smart Citation